2010
DOI: 10.1007/s10126-010-9299-6
|View full text |Cite
|
Sign up to set email alerts
|

Different Pressure Resistance of Lactate Dehydrogenases from Hagfish is Dependent on Habitat Depth and Caused by Tetrameric Structure Dissociation

Abstract: The effects of high hydrostatic pressure on lactate dehydrogenase (LDH) activities from two species of hagfish were examined. LDH from Eptatretus okinoseanus, a deep-sea species, retained 67% of the original activity even at 100 MPa. LDH activity from Eptatretus burgeri, a shallow-sea species, was completely lost at 50 MPa but recovered to the original value at 0.1 MPa. The tetrameric structure of LDH-A(4) from E. okinoseanus did not change at 50 MPa. In contrast, almost all LDH tetramers from E. burgeri disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Among these characteristics, high hydrostatic pressure is regarded as the harshest for living organisms, since it can inhibit the functions of proteins through denaturing and impairing their structures [ 2 , 3 ]. This is especially for enzymes [ 4 , 5 ] and cytoskeleton proteins [ 6 ]. Besides, at low temperatures, DNA and RNA strands tend to tighten their structures, hindering the involvement of enzymes in DNA replication, transcription and translation [ 7 ] and thus disrupting the transcription and translation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Among these characteristics, high hydrostatic pressure is regarded as the harshest for living organisms, since it can inhibit the functions of proteins through denaturing and impairing their structures [ 2 , 3 ]. This is especially for enzymes [ 4 , 5 ] and cytoskeleton proteins [ 6 ]. Besides, at low temperatures, DNA and RNA strands tend to tighten their structures, hindering the involvement of enzymes in DNA replication, transcription and translation [ 7 ] and thus disrupting the transcription and translation processes.…”
Section: Introductionmentioning
confidence: 99%
“…The Challenger Deep of the southern end of Mariana Trench in the Northwest Pacific is the deepest point (~11,000 m) in the ocean. Hydrostatic pressure there reaches 110 MPa, which can induce the disruption of salt bridges and promote irreversible unfolding and aggregation in proteins; thus, it is challenging for deep‐sea animals to maintain their protein structures and enzyme activities (Dahlhoff & Somero, ; Nishiguchi, Abe, & Okada, ; Ohmae, Miyashita, & Kato, ; Saad‐Nehme, Silva, & Meyer‐Fernandes, ). The temperatures there range from 1 to 2.5°C, and the nucleic acids tend to adopt unfavourable structures for genetic processes in the cells of animals lacking thermoregulation at these temperatures (Feller & Gerday, ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Johns and Somero [16] proposed the heat-tolerant structure of Pomacentridae LDH, and in 2008 Brindley et al [17] reported the pressuretolerant structure of Gadidae LDH-B and proposed 21 amino acid residues responsible for it. Recently, we have sequenced LDH-A genes from three hagfish species [13], examined their activities under high pressure, proposed seven amino acid residues responsible for their pressure tolerance [15,18], and found that the dissociation of tetramers caused the inactivation of Eptatretus burgeri LDH under high pressure [19]. This study aimed to determine a method for the effective expression of the LDH gene in Escherichia coli to obtain sufficient proteins to investigate the pressure-resistant structure using X-ray analysis.…”
Section: Introductionmentioning
confidence: 99%